Enhancement Of Landfill Daily Cover In Minimizing The Migration Of Heavy Metals Using Mixture Of Laterite, Peat Soils And Rice Husk - Mohamad, Nabilah (2019)
An engineered landfill is a facility designed for the safe disposal of solid wastes. The daily soil cover of a landfill is considered as the most critical components to prevent and minimize leachate generation that finally will infiltrate into the groundwater. Migration of contaminants has the potential to increase groundwater pollution. Heavy metals in water are one of the most significant environmental problems in Malaysia. Therefore, this study examines the effectiveness of admixture of laterite soil (LS), peat soil (PS) and rice husk (RH) as daily soil cover in minimizing the migration of heavy metals in landfill. Five types of metals namely cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni) and zinc (Zn) were utilized as metal contaminants. Some laboratory tests were employed in studying the compaction behavior, permeability, unconfined compression strength, cation exchange capacity (CEC), scanning electron microscopy (SEM) and surface functional groups. The adsorption capacity of laterite soil-peat soil-rice husk mixtures towards metal ions was also being studied. The adsorption capacity study was performed by batch experiments as a function of process parameters (initial concentration and contact time) was observed. Furthermore, the batch experimental data were fitted to Langmuir and Freundlich isotherms to determine the best-fit model. Next, optimization study of the laterite soil-peat soil-rice husk mixture was conducted by using Central Composite Design then followed by column studies. The CEC value of laterite soil-peat soil-rice husk mixtures was indicated in the range of 8.7 to 17.9 meq/100g which was higher than LS alone. Results from the batch study had shown that laterite soil-peat soil-rice husk mixture was found effective in removing over 90% of Cd, 99% of Cu and Cr, 85% of Ni and 83% of Zn. Meanwhile, the removal efficiency of heavy metals from the solution in the LS was less than 61%. According to the equilibrium study, the removals of Cr, Cu, Ni and Zn were controlled by monolayer adsorption onto homogeneous surface of mixtures except for Cd. The optimization study of laterite soil-peat soil-rice husk mixture revealed that 5.76 ppm initial concentration and 15 minutes of contact time were required for optimum heavy metals removal. Based on the characterization, removal efficiency and adsorption results, 50LS:40PS:10RH mixture was found to be the most suitable combination and had a good potential to be used as landfill daily soil cover. From the column test analysis, it was indicated that the relative mobility of the heavy metals was in the sequence of Ni>Zn>Cu>Cd>Cr for 50LS:40PS:10RH.